2022
DOI: 10.1002/smll.202203917
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Cu‐Porphyrin‐Based Metal–Organic Framework Nanosheet as Cathode for High‐Rate Li‐CO2 Battery

Abstract: The lithium‐carbon dioxide (Li‐CO2) battery as a novel metal‐air battery has a high specific energy density and unique CO2 conversion ability. However, its further development is limited by incomplete product decomposition resulting in poor cycling and rate performance. In this work, Cu‐tetra(4‐carboxyphenyl) porphyrin (Cu‐TCPP) nanosheets are prepared through the solvothermal method successfully. An efficient Li‐CO2 battery with Cu‐TCPP as catalyst achieves a high discharge capacity of 20393 mAh g−1 at 100 mA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…202 The dipole−quadrupole interaction between the metal sites in MOF and CO 2 provides active sites and reaction spaces for CO 2 chemical transformation. 203 Li et al studied transition metalbased eight porous MOFs (Mn 2 (bdc), Mn(dobdc), Mn-(C 2 H 2 N 3 ) 2 , Mn(HCOO) 2 , Cu(bdc), Co 2 (dobdc), Fe(bdc), and Ni 2 (dobdc); bdc = 1,4-benzenedicarboxylate, dobdc = 2,5dioxido-1,4-benzenedicarboxylate). However, they found that the Mn(II) metal centers are beneficial in reducing charging− discharging overpotential.…”
Section: Cathode Catalysts Involving Transition Metal Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…202 The dipole−quadrupole interaction between the metal sites in MOF and CO 2 provides active sites and reaction spaces for CO 2 chemical transformation. 203 Li et al studied transition metalbased eight porous MOFs (Mn 2 (bdc), Mn(dobdc), Mn-(C 2 H 2 N 3 ) 2 , Mn(HCOO) 2 , Cu(bdc), Co 2 (dobdc), Fe(bdc), and Ni 2 (dobdc); bdc = 1,4-benzenedicarboxylate, dobdc = 2,5dioxido-1,4-benzenedicarboxylate). However, they found that the Mn(II) metal centers are beneficial in reducing charging− discharging overpotential.…”
Section: Cathode Catalysts Involving Transition Metal Compoundsmentioning
confidence: 99%
“…Although the stronger affinity toward CO 2 is good for CO 2 gas capture, endowing the Mn 2 (dobdc) MOF with higher maximum discharge capacity; but, at the same time, the stronger affinity hinders the CO 2 evolution during charging (following the equation: 2Li 2 CO 3 + C = 4Li + 3CO 2 ) from the Mn 2 (dobdc) MOF, abating Li 2 CO 3 decomposition and hence resulting in the increase in the charging voltage compared to its counterpart. 202 Xu et al 203 prepared Cu-tetra(4-carboxyphenyl) porphyrin (Cu-TCPP) MOF by solvothermal process and employed it as the catalytic cathode material for Li−CO 2 batteries. The active Cu sites in Copper-based porphyrin facilitate CO 2 reduction, and the π-conjugated bonds originating from the molecule structure of porphyrin are very conducive to CO 2 capture.…”
Section: Cathode Catalysts Involving Transition Metal Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17][18][19] This specically leads to the unique pore shape/size and surface functionality in MOFs 20 and promotes their varied applications. [21][22][23][24][25][26][27][28] Typically, in gas adsorption and separation elds, many MOFs thus far have focused on separating C 2 or C 3 hydrocarbons from methane (C 1 ), which showed excellent performance and revealed promising application prospects. However, MOFs exhibiting efficient separation toward the MTO products of C 2 H 4 -C 3 H 6 mixtures have been reported only in a few MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) have been considered as promising platforms for electrocatalytic reactions due to their hierarchical pore structures, tunable compositions, and well‐dispersed metal sites. [ 31–33 ] Various MOFs and their derivatives have been used to improve the kinetics of ORR and OER in the Li‐O 2 battery. [ 34,35 ] Very recently, Yu et al.…”
Section: Introductionmentioning
confidence: 99%